"Well, good luck with that": reactions to learning of increased genetic risk for Alzheimer disease. (November 2018) - Zallen, Doris
Abstract Purpose Apolipoprotein-E (APOE ) genetic testing to estimate risk for developing late-onset Alzheimer disease is increasingly being offered without prior genetic counseling or preparation. Consumer interest continues to grow, raising the question of how best to conduct such testing. Methods Twenty-six semistructured interviews were carried out to study the reactions of individuals who had already learned of their higher risk after APOE testing had been done because of a family history of Alzheimer disease, or from genetic tests done for other health-related or general-interest reasons. Results Adverse psychological reactions were reported by a substantial fraction of the participants, including those who had specifically sought testing, those for whom the information came as a surprise, those with a family history, and those with no known history. Still, nearly all of those interviewed said that they had benefited in the long term from lifestyle changes, often learned from online sources, that they subsequently made. Conclusion The results show that people should be prepared prior to any genetic testing and allowed to opt out of particular tests. If testing is carried out and a higher risk is revealed, they should be actively assisted in deciding how to proceed.